Petri net based algorithm modelization and parallel execution on symmetric multiprocessors - Wolfmann, Aaron Gustavo; De Giusti, Armando (2022)
Fil: Wolfmann, Aaron Gustavo. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Laboratorio de Computación; Argentina.